A comparative ultrasound evaluation of two cases of prenatal and postnatal hydrocele - Afodun, Adam Moyosore; Quadri, Khadijah Kofoworola; Ayinde, Taofeek Olanrewaju; Odumeru, Emmanuel Adeyemi; Mukangendo, Mecthilde; Okesina, Akeem Ayodeji (Journal of Biomedical Sciences, 2024)
Background: Ultrasonography plays a major role in distinguishing extra-testicular and intratesticular abnormalities. A hydrocele of a male fetus characterised by a ‘half-moon’ hypoechoic fluid rim around the testis was observed. In adults, it is evidenced by serous fluid collection between the parietal and visceral layers of the tunica vaginalis. Case presentation: A comparative analysis of two cases of in-vitro and in-vivo diagnosis of hydrocele in a woman at 30 weeks of gestation and a 38-year-old male was made. The crux of the report on the prenatal hydroceles’ variety showed constancy of unchanged fluid volume, suggesting it to be a non-communicating type. The report is contrary to a communicating variety that enlarges throughout gravidae with possible inguinal hernia. There are few comparative hydrocele case sonograms in literature. Conclusion: Ultrasound is a safe, reliable, and accurate method for evaluating patients with scrotal diseases, and the approach to dual sono-diagnosis is surgery when unresolved to eliminate spermatic cord compromise.